2011
DOI: 10.5402/2011/759893
|View full text |Cite
|
Sign up to set email alerts
|

Secondary Forest Succession in the Mata Atlantica, Brazil: Floristic and Phytosociological Trends

Abstract: This study aimed at understanding the dynamics of ecological processes and the use of secondary forests in Santa Catarina state (Brazil). The data base for these studies was formed through forest inventories carried out in the three forest types of the state. The results of this study demonstrate that the patterns of diversity are very similar among the three forest types; however, the species compositions among the types are quite different. A total of 343 woody species belonging to 73 families were found in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
24
1
6

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 29 publications
(27 reference statements)
3
24
1
6
Order By: Relevance
“…This is evident in the presence of more early successional tree and grass species in the youngest plot (plot I). Also, the observation in this study showed that older plots had the highest diversity which is in line with the assertion of Fantini et al (2011), who stated that species diversity is often greatest during mid-successional stages that contain both early and late successional species.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…This is evident in the presence of more early successional tree and grass species in the youngest plot (plot I). Also, the observation in this study showed that older plots had the highest diversity which is in line with the assertion of Fantini et al (2011), who stated that species diversity is often greatest during mid-successional stages that contain both early and late successional species.…”
Section: Discussionsupporting
confidence: 77%
“…The dominance of Trema orientalis (L.) Blume, an early successional species, in the youngest plot (plot I) shows that the plot is still undergoing some early stage of colonisation. This is in line with the assertion of Fantini et al (2011) who opined that during the early stages of secondary succession, species such as Trema micrantha (L.) Blume have high densities and dominance when they occur. There was also an abundance of some species in the older plots, such as Deinbollia pinnata (Poir.)…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Despite variations in methods and diversity estimates among various studies (Chazdon 2008), the unidirectional increase in species richness in our study was supported even for other stem size inclusion criteria (see Appendix 2). The diversity of the late successional forest (H' canopy = 3.24) is comparable to old-growth forests (H'= 3.22-5.00) in the Atlantic Forest region (Liebsch et al 2007;Martini et al 2007;Siminski et al 2011), and suggests that 59 years of abandonment is sufficient for recovering a large part of the forest diversity and composition originally found in the study region. Despite our findings, the recovery of forest diversity is not necessarily followed by forest functionality (Díaz & Cabido 2001), which may take a longer time period and limit ecosystem processes (Liebsch et al 2008).…”
Section: Discussionmentioning
confidence: 73%
“…Aide et al (2000) reported that a 40 year interval is necessary for recovery of mature tropical forest structure and richness in abandoned pastures of Puerto Rico, but more than 60 years to reach similar species composition to the original forest. In Southern Brazilian Atlantic forests, even though diversity increased after 15-30 years (up to 95 woody species.ha -1 ), only a small number of species become structurally important over this time, suggesting that these communities will need many more decades to recover their original structure (Siminski et al 2011). Klein (1980) estimated more than 90 years to recover the climax diversity and Suganuma and Durigan (2015) projected up to 270 years to recover the proportion of slow growth tree individuals of these ecosystems in Brazil.…”
Section: Introductionmentioning
confidence: 99%